Mikobiota pada Buah Cabai untuk Pengendalian Hayati Colletotrichum capsici - Okky Setyawati Dharmaputra; Lisdar Idwan Sudirman; Melly Fitriani (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Colletotrichum capsici is a pathogenic fungus causing anthracnose on various tropical fruits, especially chilli. Biological control agents have been used as an alternative method to control postharvest diseases. This study aims to examine the antagonistic potential of mycobiota on red chilli fruit against C. capsici. The pathogen was obtained from diseased red chilli fruits collected from three traditional markets in Municipality of Bogor, isolated on potato dextrose agar (PDA) medium containing chloramphenicol (100 mg L-1). Candidates of antagonistic mycobiota were isolated from healthy chilli fruits using serial diution method, followed by pour-plate method on PDA medium containing chloramphenicol (100 mg L-1). C. capsici isolate BIO51046 showed highest pathogenicity on chilli fruit var. IPB Perbani compared to other isolates. Seven isolates of filamentous fungi and 7 yeast isolates were obtained from healthy chilli fruits. Test of antagonism using dual culture method obtained 3 filamentous fungal isolates (Plectosphaerella cucumerina, MF2 and Aspergillus flavus) and 1 yeast isolate (Issatchenkia orientalis) which inhibited the growth of C. capsici BIO 51046 more than 70%. Plectosphaerella cucumerina and I.orientalis did not cause any diseases on chilli fruits var. IPB Perbani. Therefore, these 2 isolates were considered as potential antagonist against C. capsici BIO51046 as the causal agent of anthracnose of chilli